Research on the degradation mechanism of the lead-glazed cups from the ‘Yangtze River estuary No. 2’ shipwreck - Yan He; Weidong Li; Yang Zhai; Luo Zhao; Xiaoke Lu; Changsong Xu (Open Ceramics, 2023)
The ‘Yangtze River Estuary No. 2’ shipwreck of the Qing Dynasty (1636–1912 CE) is one of the most well-preserved ancient wooden shipwrecks discovered underwater in China to date. Unfortunately, most green lead-glazed cups salvaged out of the shipwreck have severely degraded and generally blackened in the underwater environment. In this study, the degradation mechanism of the lead glaze in the underwater environment were investigated in depth. It was found that the degradation of lead glaze involved several complex chemical and physical processes. The special environmental conditions caused by the corrosion of iron components in the shipwrecks may be an important reason for the loss of Si elements in corrosion layers. The appearance changes of the green glaze are related to the leaching of Cu2+ ions and the gradual transformation to a lead-rich corrosion layer. The iridescent phenomenon may be related to the thin-film interference of the laminated corrosion layers.